The Route Choice Support System for Disabled Pedestrian using Wheelchair - MINAMI, Masaaki; TAMURA, Youichi; YOSHITAKE, Kazunori (INFRASTRUCTURE PLANNING REVIEW, 2002)
Routes between an origin and a destination are restricted for a pedestrian using a wheelchair because of the existence of obstacles Such obstacles are: roughness, inclination, railroad crossings and so forth. The allowable level of an obstacle is different based on the pedestrian's physical condition. In this paper, the computer-aided route choice support system has been developed A pedestrian using a wheelchair inputs an origin and a destination and chooses allowable levels of obstacles on a route. As an output of the system, the shortest route between them, which satisfies the allowable levels of obstacles, is calculated as a recommended route. The pedestrian can choose a suitable route to get to the destination based on his/her own physical condition.